III Ordinary Meeting of the Council of Chiefs and Heads of State and Government of the Union of South American Nations (UNASUR) Presidential Declaration of Quito - Suramericanas, Unión de Naciones (2016)
The Presidential Declaration of Quito, Ecuador presented on August 10, 2009 at the III Ordinary Meeting of the Council of Chiefs and Heads of State and Government of the Union of South American Nations (UNASUR).